The global ranking tournament: A dialectic analysis of higher education in South Africa - Dlamini, R (South African Journal of Higher Education, 2016)
The unprecedented changes in the university, to homogenizing the principle of identity in association with the dominant class [world-class universities] supports a very limited conception of higher education. The mantras of global rankings have permeated South Africa’s institutions of higher education, yet the rankings’ constructs are subjective, and inadequate in nature. This paper uses aspects of Jurgen Habermas’s ‘Critical Theory of Societal Development’ as its lens to account for the implications of South African universities joining the ‘super-league’ universities. The efforts being made to achieve a kind of iconic status are contradictory to making education a bridge to achieve equality.